PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 13 PADANG - Malinda, Ika (Departemen Matematika, 2023)
The study of mathematics aims to teach pupils how to solve mathematical problems. However, kids' problem-solving skills remain poor. This is because the learning paradigm employed to increase pupils' mathematical problem-solving skills is insufficient. Problem-based learning is one solution. This study reviews the development and effects of Problem Based Learning (PBL) on mathematics problem-solving skills. Descriptive and quasi-experimental methods were used in this posttest-only non-equivalent control group study. This study included 2022/2023 SMP Negeri 13 Padang grade VIII students. The experimental class, VIII.5, was sampled, while the control class, VIII.4, was randomly picked. It included quizzes and a final exam. The hypothesis test for the final exam, which yielded a P-value of 0.000, and the mean quizzes showed that Problem-Based Learning improved students' problem-solving skills.Keywords– Problem Based Learning Model, Conventional Model, Mathematical Problem Solving Ability